2011
DOI: 10.1007/s10567-010-0082-z
|View full text |Cite
|
Sign up to set email alerts
|

Family Adjustment to Childhood Cancer: A Systematic Review

Abstract: This systematic review integrates qualitative and quantitative research findings regarding family changes in the context of childhood cancer. Twenty-eight quantitative, 42 qualitative, and one mixed-method studies were reviewed. Included studies focused on family functioning, marital quality, and/or parenting in the context of pediatric cancer, were written in English, and were published between 1996 and 2009. Overall, qualitative findings show that families alter roles, responsibilities, and day-to-day functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
330
0
18

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 323 publications
(360 citation statements)
references
References 112 publications
(322 reference statements)
12
330
0
18
Order By: Relevance
“…However, cancer-related distress during the adolescent hospitalization was high for both variables assessed; self-perceived distress (median = 10) and effort to cope with the situation (median = 9). According to existing literature on this topic [23], our findings revealed that parents experience great distress throughout the process and even in survivorship. Therefore, they could benefit from interventions targeted to offer support, counseling, encouragement or even to allow expression of their worries and feelings [23].…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…However, cancer-related distress during the adolescent hospitalization was high for both variables assessed; self-perceived distress (median = 10) and effort to cope with the situation (median = 9). According to existing literature on this topic [23], our findings revealed that parents experience great distress throughout the process and even in survivorship. Therefore, they could benefit from interventions targeted to offer support, counseling, encouragement or even to allow expression of their worries and feelings [23].…”
Section: Discussionmentioning
confidence: 64%
“…According to existing literature on this topic [23], our findings revealed that parents experience great distress throughout the process and even in survivorship. Therefore, they could benefit from interventions targeted to offer support, counseling, encouragement or even to allow expression of their worries and feelings [23]. Professionals responsible for cancer patients need to assess the impact of cancer diagnosis and treatments on parents' well-being, in order to prevent future complications and enhance positive adaptation.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Studies even have indicated the existence of the symptoms of the posttraumatic stress syndrome in mothers following treatment (Stuber et al, 1996;Kazak et al, 1997). Since 1970, many investigations have been carried out on different aspects of childhood cancer, which mostly have focused on the parent-child adaptability process (Khoury, 2013), psychological impacts of diseases on children and families (Long and Marsland, 2011), and the effects of diseases on the family system (Patterson et al, 2004;Woodgate, 2006;Tedford and Price, 2011). In the majority of these studies, psychological aspects of the disease and family-child adaptability (Khoury, 2013) have been examined but less attention has been paid to the effect of daily care of children with cancer on mothers' health.…”
Section: Introductionmentioning
confidence: 99%